Pierre Robin sequence in association with tracheoesophageal fistula and esophageal atresia - Baltrak, Yusuf Atakan; Varlikli, Onursal (Indian Journal of Child Health, 2019)
The first symptom of esophageal atresia and tracheoesophageal fistula is the inability to eat and respiratory distress after feeding. The coexistence of Pierre Robin Sequence (PRS) with esophageal atresia and tracheoesophageal fistula is a rare clinical condition. In infants with PRS, evaluation of respiratory and nutritional problems is important. The coexistence of esophageal atresia and tracheoesophageal fistula leads to increased nutritional and respiratory problems. Problems that may occur in the airways may occur late. In this case report, we aimed to present a case of neonatal infant with rare esophageal atresia, tracheoesophageal fistula, and PRS.